Geochemistry of nodules from a young seamount - Lonsdale, Peter; Burns, Virginia Mee; Fisk, Mary B (Supplement to: Lonsdale, P et al. (1980): Nodules of Hydrothermal Birnessite in the Caldera of a Young Seamount on JSTOR. The Journal of Geology, 88(5), 611-618, http://www.jstor.org/stable/30066087, 1980)
Manganese nodules made of radiating rods of well crystallized birnessite were sampled at 8 degree 481.2'N, 103 degree 53.8W, 1875 m below sea level by a dredge that also collected hyaloclastite and basaltic talus. The nodule field is on the floor of a caldera within a young tholeiitic seamount and was discovered and photographed during a deep-two survey. It is interpreted as a brecciated hydrothermal deposit, crystallized from an amorphous manganese oxide precipitate that formed when seawater-based hydrothermal fluids mixed with oxidized seawater. The nodules and surrounding igneous rocks have subsequently been encrusted with hydrogenous ferromanganese oxides.